Community Structure of Mangrove Vegetation in Sapat Village, Kuala Indragiri District, Indragiri Hilir Regency, Riau Province - Martha, Rezky Dwi; Zulkifli, Zulkifli; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Mangroves are very productive wetlands and can live in areas still influenced by tides. This research was conducted in November - December 2023 in the mangrove ecosystem of Sapat Village, Kuala Indragiri District, Indragiri Hilir Regency, Riau Province. This study aimed to determine the structure of mangrove vegetation communities in Sapat Village. This study used the survey method, and three stations were used. Mangrove species found include Avicennia alba, Sonneratia alba, S.caseolaris, S.ovata, Nypa fruticans, Rhizophora apiculata, Bruguiera parviflora, B.gymnorhiza, B.sexangula, and Achantus ebracteatus. Mangrove vegetation density at station I has very dense criteria, station II medium criteria, and III has sparse criteria. From the index aspect, the mangrove vegetation community has a diversity value (H'), which is classified as moderate, with sufficient productivity, which has a value ranging from 1.33-1.68. The uniformity value (E) of stations I and II is in the moderate category, which ranges from 0.57-0.58, and station III is classified as a high category with a value of 0.73. Moreover, the value of the dominance index (C) is classified as low, ranging from 0.21-0.3 based on the significant value. The type of N.fruticans dominates because they have a more excellent value than other species seen at each station in both categories of trees, saplings, and trees.